Origins of institutionalized community development in Costa Rica. (UNED Research Journal, 2010)
Institutionalized community development in Costa Rica evolved within the “inward-oriented development model,” driven by an “Epistemic Network” centered at the Economic Commission for Latin America. The model was designed to replace structures and non-rational social relations inherited from the “outward growth model” (agricultural exporter model). By the late 1970s, countries that implemented the model suffered a foreign debt that minimized the possibility of state intervention in economic growth. In Costa Rica, along with the fall of model, the institutionalized program declined, but during its first ten years, the program of community development through Development Associations had been efficient as a companion to modernization of agriculture and industry. Associations were widespread geographically, but concentrated in the border areas where the population was moving. They channeled state funding and local resources for road works and infrastructure that provided public services. With the crisis, the associations were criticized. The political leadership accused them of politicking; the social-democratic intellectuals of having raised no major national issues; and the academic left of having abandoned the effort of popular participation. But the associations had other goals, and they were successful in reaching them.
Keywords: Community organizations; Cota Rica history; development; economic models.